2016
DOI: 10.1371/journal.pone.0165131
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetic Mellitus Is a Risk Factor for Nasopharyngeal Carcinoma: A 1:2 Matched Case–Control Study

Abstract: BackgroundDiabetes has been identified as an adverse prognostic variable which associated with an increased mortality in various cancers, including colorectal, lung, and breast cancers. However, previous studies provided inconsistent results on the association between diabetes and nasopharyngeal carcinoma (NPC). The main aim of this study was to investigate the associations between diabetes mellitus and the survival of NPC patients.MethodsThis study was designed as a 1:2 matched case–control study. Cases were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The current AJCC/UICC stage classification is the main guideline for NPC risk stratification in clinical practice. However, this classification does not consider several variables that have been suggested as prognostic factors in NPC, such as age, gender, LDH, comorbidities, and, in particular, EBV DNA (11)(12)(13). Therefore, a more comprehensive prognostic model is urgently needed to accurately predict patients' clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current AJCC/UICC stage classification is the main guideline for NPC risk stratification in clinical practice. However, this classification does not consider several variables that have been suggested as prognostic factors in NPC, such as age, gender, LDH, comorbidities, and, in particular, EBV DNA (11)(12)(13). Therefore, a more comprehensive prognostic model is urgently needed to accurately predict patients' clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor, node, metastasis (TNM) staging system, which continues to be a globally recognized standard for assessing the prognosis of NPC, has been criticized as barely satisfactory, as it does not account for important prognostic factors, such as Epstein-Barr virus (EBV) DNA and serum lactate dehydrogenase (LDH) levels (11)(12)(13). Therefore, this study aimed to evaluate several potential prognostic factors and construct a prognostic score to classify risk status and identify suitable patients with stage III-IVa NPC that could benefit from IC, using data from a large cohort of patients.…”
Section: Introductionmentioning
confidence: 99%
“…All studies retrospectively analyzed data. Three studies reported the median follow-up period, 20 , 21 , 23 with a range between 34.6 and 66.0 months. Four studies adopted multivariate analysis method, 19 22 but only one study used a matched design to select control patients.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies adopted multivariate analysis method, 19 22 but only one study used a matched design to select control patients. 20 DM was identified in the cohorts using blood glucose test results validated by medical records in all five studies.…”
Section: Resultsmentioning
confidence: 99%
“…Anti-HBV treatment may improve the prognosis of HBV-infected NPC patients [44]. Type 2 diabetes, a risk factor for NPC, is associated with a poor prognosis in NPC [45]. High-titer malaria antibodies can diagnose NPC.…”
Section: Discussionmentioning
confidence: 99%